Ensayo de interpretación de la plataforma continental geofísica del Caribe - Durán S. Luis Guillermo (Caldasia)
This paper is an attempt to interpret the negative isostatic anomaly of the Western Caribbean Sea on the basis of the new criterion used by professor M. Ewing et al. in their interpretation of the island arc in Pto. Rico area. The proposed interpretation is a departure from the previous one generally accepted, which was based on the tectogene theory of professor H. H. Hess. In other words, the negative anomaly is attributed here to the sediments' thickenning and possible geosynclinal structure, rather than to deeper tectogenic deformation involving sial and sima. A geomorphologic interpretation of the Caribbean continental shelf is offered on this basis.  The interpretation is locally based on correlation of the isostatic anomaly values (pendulum) with surface gravimetric values (gravity meter) in the Colombian coastal area (near Barranquilla), as compiled by the International Geophysical Year's Colombian Gravity Committee, and general stratigraphic and structural data of the Atlantic coast.  A brief account and analysis of gravimetric principles and previous gravity works and their interpretations is given, especially in connection with isostasy and the general island arc problem. The paper aims mainly at encouraging interest toward cooperative research and further geophysical detail work in the Western (Colombian) Caribbean. Sea area.